The Effect ofFourth Century (HIJRI)Compendiums on Facilitating & Teaching Arabic Grammar The Book "Al-Wadih" by Al-Zobaidias a Sample - Aouarib, Salim (Milev Journal of Research and Studies, 2021)
Our research paper aims to monitor the effect of the 4th century grammatical compendiums on facilitating and teaching the Arabic grammar, by selecting to Al-Zobaidi’s book “Al-Wadih” as an example through which we seek to simplify and teach the approaches of the 4th century gramaticians in facilitating and teaching grammar, and the approach of Al-Zobaidi in particular. By authoring this book, Al-Zobaidi did not criminalize himself as a leader of facilitation and education; this is why we aim through this study to highlight the significance of his book “Al-Wadih” in facilitating and teaching the Arabic grammar,by means of a unique curriculum that was carried out in the fourth century (HIJRI). After addressing the approach of the 4th century (HIJRI) in general, which should render us to raise the questionon the gramaticians of the 4th century (HIJRI)and on whether they had aneffect on facilitating and teaching the Arabic grammar? What is the value of Al-Zobaidi'sAl-Wadih book, and what is its status? Seeking to meet the objectives, it has been sought to adopt a methodology based on clarifying some of the concepts and terminologies of the study, then to address the approach of the fourth century toward facilitation, and then to study the content of Al-Wadih book, the approach of the Zebeidi in it, and its effect on facilitating the grammar.Following that analytical descriptive approach, this is why, using inference and proof, we have concluded with the following results: Al-Zobaidi'sAl-Wadih book has a clear and profound effect on facilitating and teaching the rules of the Arabic grammar to beginners, for it is characterized by its ability, competence and the right approach based on the learners’ level